Formidable Heritage; Manitoba's North and the Cost of Development 1870 to 1930 - Morrison, William R. (Labour / Le Travail, 2005)
The article reviews the book, "Formidable Heritage: Manitoba's North and the Cost of Development 1870 to 1930, by Jim Mochoruk.